Optimasi Jalur Distribusi Menggunakan Pendekatan Algoritma Genetika - Saputra, Arie; Fadhilah, Desi (Universitas Teuku Umar, 2024)
Management and planning of transportation distribution channels are important in increasing the company's operational efficiency. Optimal distribution arrangements can reduce transportation costs and time, as well as increase product competitiveness in the market. One method used to determine the best distribution route is the Traveling Salesman Problem (TSP), which helps companies achieve maximum efficiency. This research was carried out at the AMDK CV company. Tirta Naga Lestari (TNL) as a case study to analyze product distribution to 11 locations in Aceh. Unplanned product distribution causes high shipping costs. A genetic algorithm (GA) approach is used to find the optimal distribution route. Previous research shows that GA effectively solves complex transportation problems, such as Vehicle Routing Problems (VRP) and transportation scheduling. This research is a development of the use of the GA method for multiple routing case studies where a route repetition process occurs. This is interesting because previous studies only focused on developing GA methods for single or multiple routing cases but there was no route repetition process (looping). This research aims to determine the optimal distribution path for cases with multiple routing and repetition of the same route. The different constraints of the solved cases require a more adaptive GA approach. From the results obtained, it is proven that it can minimize total distribution costs of IDR 2,900,000,- with an efficiency of 37.52%. This study is proven to be able to use the GA approach to solve multiple routing problems with route repetition, thus helping to find optimal route solutions that are more efficient for product distribution.